Anisotropic noble metal nanoparticles: Synthesis, surface functionalization and applications in biosensing, bioimaging, drug delivery and theranostics. (February 2017) - Paramasivam, Gokul; Kayambu, Namitharan; Rabel, Arul Maximus; Sundramoorthy, Ashok K.; Sundaramurthy, Anandhakumar
Graphical abstract: Abstract: Anisotropic nanoparticles have fascinated scientists and engineering communities for over a century because of their unique physical and chemical properties. In recent years, continuous advances in design and fabrication of anisotropic nanoparticles have opened new avenues for application in various areas of biology, chemistry and physics. Anisotropic nanoparticles have the plasmon absorption in the visible as well as near-infrared (NIR) region, which enables them to be used for crucial applications such as biological imaging, medical diagnostics and therapy ("theranostics"). Here, we describe the progress in anisotropic nanoparticles achieved since the millennium in the area of preparation including various shapes and modification of the particle surface, and in areas of application by providing examples of applications in biosensing, bio-imaging, drug delivery and theranostics. Furthermore, we also explain various mechanisms involved in cellular uptake of anisotropic nanoparticles, and conclude with our opinion on various obstacles that limit their applications in biomedical field. Statement of Significance: Anisotropy at the molecular level has always fascinated scientists and engineering communities for over a century, however, the research on novel methods through which shape and size of nanoparticles can be precisely controlled has opened new avenues for anisotropic nanoparticles in various areas of biology, chemistry and physics. In this manuscript, we describe progress achieved since the millennium in the areas of preparation of various shapes of anisotropic nanoparticles, investigate various methods involved in modifying the surface of these NPs, and provide examples of applications in biosensing and bio-imaging, drug delivery and theranostics. We also present mechanisms involved in cellular uptake of nanoparticles, describe different methods of preparation of anisotropic nanoparticles including biomimetic and photochemical synthesis, and conclude with our opinion on various obstacles that limit their applications in biomedical field.